2021
DOI: 10.1111/jir.12834
|View full text |Cite
|
Sign up to set email alerts
|

Oral health care and service utilisation in individuals with Rett syndrome: an international cross‐sectional study

Abstract: Background There is a dearth of literature available on the comparative oral health status of those with Rett syndrome (RTT) despite diurnal bruxism being a supportive diagnostic criterion for the disorder. This study was designed to investigate the dental experiences of individuals with RTT in terms of perceived at‐home and professional dental care. Methods Using data in the InterRett database, provided by English‐speaking families of individuals with a confirmed MECP2 genetic mutation, the study investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Barriers in the UK to care within the public sector include waiting list issues (14.1%) and cost (5%) 48 . One reason why cost may not have been perceived as a major barrier for most families in the present study was that the families placed a high value placed on oral health and therefore on dental attendance, as noted in a previous study 28 . Another reason why cost may not have been perceived by many as a major barrier for dental access may again be sociodemographic factors.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…Barriers in the UK to care within the public sector include waiting list issues (14.1%) and cost (5%) 48 . One reason why cost may not have been perceived as a major barrier for most families in the present study was that the families placed a high value placed on oral health and therefore on dental attendance, as noted in a previous study 28 . Another reason why cost may not have been perceived by many as a major barrier for dental access may again be sociodemographic factors.…”
Section: Discussionsupporting
confidence: 47%
“…24 Diurnal bruxism is the most frequently reported oral presentation, 25,26 and there are various management approaches reported in the published literature in RTT, ranging from tooth restorations for worn or fractured tooth structure to more novel approaches such as bite planes and even acupuncture. 24 While bruxism in RTT has been explored and some studies of the overall oral health experiences of those with RTT have been completed, including oral disease incidence, type and modality of treatment received, 25,[27][28][29] little is known regarding barriers faced by individuals with RTT for accessing timely and appropriate oral health care. An Australian population-based retrospective study 27 found that dental extractions were more likely to have occurred in individuals with RTT living at home in households with a low annual household income.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other stereotypies are also prevalent in patients with RTT, and these too can emerge differently, such as bruxism 26,28 and shifting of the weight 34 . Individuals with bruxism were also more inclined to access dental services 43 ; however, the risk of bruxism appears to decline with age 44 . Oral motility was also affected by dystonic and dyskinetic movements 45 .…”
Section: Resultsmentioning
confidence: 99%